2019
DOI: 10.1002/14651858.cd012442.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GD2 antibody-containing immunotherapy postconsolidation therapy for people with high-risk neuroblastoma treated with autologous haematopoietic stem cell transplantation

Abstract: Anti-GD2 antibody-containing immunotherapy postconsolidation therapy for people with high-risk neuroblastoma treated with autologous haematopoietic stem cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Dinutuximab is used in combination with interleukin-2, granulocyte–macrophage colony-stimulating factor, and isotretinoin (13- cis- retinoic acid) for maintenance treatment of pediatric patients with high-risk neuroblastoma who has achieved at least a partial response to first-line multiagent, multimodality therapy 32 . Dinutuximab gave an increased the 2-year event-free survival and overall survival when compared to standard treatment in phase III trials 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Dinutuximab is used in combination with interleukin-2, granulocyte–macrophage colony-stimulating factor, and isotretinoin (13- cis- retinoic acid) for maintenance treatment of pediatric patients with high-risk neuroblastoma who has achieved at least a partial response to first-line multiagent, multimodality therapy 32 . Dinutuximab gave an increased the 2-year event-free survival and overall survival when compared to standard treatment in phase III trials 33 .…”
Section: Discussionmentioning
confidence: 99%
“…According to the report, there is a unique coincidence of neonatal lupus and NBL (42). In addition, antigen processing and presentation are also involved in the treatment of NBL (43, 44). The chemokine signaling pathway (45, 46) and the cytokine-cytokine receptor interaction (47) also play a role in the occurrence and development of NBL.…”
Section: Discussionmentioning
confidence: 99%
“…Progression of neuroblastoma during or following treatment with anti-GD2 mAbs also may result from insufficient tumor cell exposure to the antibody, a response by immune effector cells that is inadequate to induce ADCC or CDC, or inherent resistance of the patient's neuroblastoma cell line to antibody therapy (75). Nevertheless, a Cochrane Database Systematic Review published in April 2019 concluded that, based on the results of the pivotal phase III ANBL0032 trial, the evidence base favors "dinutuximab-containing immunotherapy compared to standard therapy concerning overall survival and event-free survival in people with high-risk neuroblastoma pre-treated with autologous HSCT" (101).…”
Section: Neuroblastomamentioning
confidence: 99%